RELIGIUSITAS SEBAGAI PREDIKTOR TERHADAP KESEHATAN MENTAL STUDI TERHADAP PEMELUK AGAMA ISLAM - Ghozali Rusyid Affandi; Dewanti Ruparin Diah (University of Merdeka Malang, 2011)
Abstract Modern era that is more focus on materialism, individual and demand on the quickly change. It makes people will get such problem if they cant adjust their self. The incapability in adaptation will make someone get anxiety, frustration and depression quickly; those are manifestation of mental illness. This condition will be worse if someone has not paid attention religion aspects of his life. This is caused by the base of religion if one of four dimension which influence somebodys life. If one of them is unfulfilled so human function will be disturbed i.e. mental illness. The aimed of this research is to know whether religiosity is the factor that effect mental illness. The sampling technique in this research is quota sampling and accidental sampling. Subject of this research is 18-40 years old and Moslem with the total number of 82 people. The instrument for collecting data is mental illness scale and religiosity scale. The result of regression analysis was indicated that F (54,068) F table and r2 = 0,403. So the hypothesis is accepted, this means religiosity can predict mental illness with the prediction capacity is 40,3%. Keyword: Mental Health, Religiosity, Moslem.